PRODUCTIVITY AND EFFECTIVE DEMAND: ASSESSING THE DISAGGREGATE PUBLIC SPENDING - Zavaleta, Josué; Cruz, Moritz (Investigación Económica, 2019)
In this paper, we attempt to support the argument regarding the endogeneity of productivity to effective demand. Unlike most of the works on the topic, we focus on the role that both public investment and public consumption have on productivity. We suggest, at the theoretical level, that public investment has unambiguously positive effects on productivity, whereas the effect of public consumption is ambiguous, being not necessarily large or positive. Our econometric results, using data of selected Latin American economies, support the previous argument. The policy recommendation that follows from these results is that an expansionary fiscal policy based on public investment can indeed enhance the productivity evolution and consequently economic growth and development. PRODUCTIVIDAD Y DEMANDA EFECTIVA: EVALUANDO EL CASO DEL GASTO PÚBLICO DESAGREGADO RESUMEN En este trabajo nos proponemos sustentar el argumento referente a la endogenidad de la productividad respecto a la demanda agregada. A diferencia de la mayoría de los trabajos en el tema, nos enfocamos en el papel que el gasto público tanto en consumo como en inversión tiene sobre la productividad. Sugerimos, a nivel teórico, que el gasto público en inversión tiene sin lugar a dudas efectos positivos en la productividad, mientras que el gasto público en consumo tiene efectos ambiguos, siendo no necesariamente grandes o positivos. Nuestros resultados econométricos, usando datos de una muestra selecta de economías de América Latina, validan el argumento previo. La recomendación de política que sigue a estos resultados es que para incrementar la productividad, así como el crecimiento y el desarrollo económicos, la política fiscal expansiva debe estar basada principalmente en gasto en inversión.